PLACE OF SHANGHAI COOPERATION ORGANIZATION'S IN THE NEW WORLD ORDER - Fatih Mehmet Bulut; Nihal Aghazade (European Scientific Journal, ESJ, 2015)
Shanghai Cooperation Organization is on its way to be one of the biggest challengers of the unipolarity. The article particularly focuses on the security issues of not just the member states but the region as well. Security cases top the agenda of SCO states.